Characterisation of the glycoside hydrolase domain of a novel bi-functional metagenomic clone for use in the biofuel production industry - Swanepoel, Craig C. (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.